Investigating the predictive value of vascular endothelial growth factor in the evaluation of treatment efficacy and prognosis for patients with non-surgical esophageal squamous cell carcinoma - Kong, Ze; Sun, Fei; Meng, Qinghong; Zhou, Mengyun; Yu, Jingping; Hu, Lijun (Frontiers in Oncology, 2022)
In this study, we aim to investigate the predictive value of serum vascular endothelial growth factor (VEGF) in evaluating treatment efficacy and long-term prognosis for patients with non-surgical esophageal squamous cell carcinoma (ESCC). The patients diagnosed with ESCC by histopathology who didn’t receive surgical treatment were retrospectively analyzed. Through follow-up and prognostic analysis, we explored the value of serum VEGF changes before, during, and after radiotherapy for predicting treatment efficacy, and identified important indicators to construct the predictive model. Eighty-four patients were enrolled in this study, and the objective response rate (ORR) after treatment was 75.0%. The serum VEGF before, during and after radiotherapy were 108.2 ± 38.4, 98.6 ± 20.3 and 96.9 ± 20.0pg/ml, respectively. Staging and serum VEGF during radiotherapy were the independent factors affecting the treatment efficacy of non-surgical ESCC patients (OR=0.182 and 0.959, P<0.05). The median overall survival (OS) and progression-free survival (PFS) were 24.4 and 15.8 months. The 3-year, 5-year, 10-year OS rates and PFS rates were 35.7%, 26.2%, 14.4%, and 26.2%, 22.6%, 12.3%, respectively. By performing COX regression analysis, we found that the TNM stage, changes of VEGF after radiotherapy (∆VEGF2), and endoscopic histopathological response were the independent prognostic factors for OS and PFS (P<0.05). The R2 of the constructed prediction model was 0.328 and 0.362, and the C-index was 0.697 and 0.708, respectively. The follow-up time-dependent AUC showed that the predicted AUC was stable and greater than 0.7 as the follow-up time increased. For patients with non-surgical ESCC, those with low VEGF levels during radiotherapy had better treatment efficacy, and those with significant VEGF reduction after radiotherapy had a better prognosis. In summary, our results demonstrate that it is feasible to construct a model to evaluate and predict the efficacy and prognosis of patients with non-surgical ESCC based on serum VEGF measurement.